Space Debris and Its Impacts on Space Exploration and Mitigation Strategies - Belay Sitotaw Goshu (Britain International of Exact Sciences (BIoEx) Journal, 2025)
The increasing proliferation of space debris from 1960 to 2021 poses significant environmental challenges for space operations. This study aims to analyze the historical trends in space debris creation, focusing on the rise of payloads and rocket debris, and assess their implications for space sustainability. Utilizing data from various space agencies and surveillance networks, we examined the growth patterns of different object types, including debris, payloads, rocket bodies, and others. The analysis revealed a sharp increase in payload deployment since 2000, driven by the rise of satellite-based technologies and the commercialization of space. Similarly, rocket debris has also seen an uptick, though at a slower rate. Debris objects, which account for the largest share, pose significant risks due to their potential to cause collisions and further fragmentation. These trends highlight the urgency of implementing effective debris mitigation strategies to prevent the Kessler Syndrome a cascade of collisions that could render certain orbits unusable. Key mitigation strategies discussed include Active Debris Removal (ADR), end-of-life disposal plans, improved space traffic management, and design-for-demise techniques. The study underscores the need for international cooperation and the adoption of innovative technologies to ensure the sustainable use of space. The findings provide valuable insights for policymakers and stakeholders in developing comprehensive frameworks for space environmental management.